Identification of UHT Granulites in the Pan-African Dahomeyide Suture Zone in SE Ghana: Implications for Evolution of Collisional Orogens. (11th May 2022) - Aidoo, Felix; Zhang, Qiang-Qiang; Zhang, Shao-Bing; Nude, Prosper M
Abstract: This study presents the petrology, geochemistry, U–Pb ages, Lu–Hf and oxygen isotope compositions of Adaklu mafic granulites (ADMGs), from the Pan-African Dahomeyide suture zone in southeastern Ghana. The ADMGs show mafic precursor with low-K tholeiitic affinity. They display convex rare earth and trace elements characteristics without any obvious anomalies of Eu, Ti, Nb and Ta. The geochemical characteristics of ADMGs mimic those of N-MORB. Zircon U–Pb dating on the ADMGs reveals granulite facies metamorphic ages of ca. 595–602 Ma. However, a few zircons yield relatively older apparent 206 Pb/ 238 U ages of ca. 620 Ma, representing prograde metamorphic age. ADMGs preserve mean zircon εHf (t) values of +7.0 to +9.7 and δ 18 O values of 6.1–8.0‰. Based on petrographic observations, geothermobarometric calculations using conventional thermobarometry, mineral equilibria modeling, Ti-in-zircon and Zr-in-rutile thermometers reveal peak granulite facies P–T conditions of 0.95–1.2 GPa/940–1000°C, and retrograde amphibolite facies conditions of 0.83–0.93 GPa/575–710°C. The prograde metamorphic stage is inferred to be amphibolite or eclogite facies metamorphism. Hence, a clockwise a P–T–t path is proposed for the ADMGs. The overall results indicate that ADMGs are ultra-high temperature (UHT) granulites, and the protolith is altered oceanic crust consumed during the Pan-African collisional events. Asthenospheric upwelling induced by lithospheric delamination in the earliest extension of the thickened orogen, or by slab break-off in the background of collision may have provided the additional heat for UHT granulite facies metamorphism.